Use of mechanistic principles to make modified natural rubber latex products by emulsion polymerisation - Subramaniam N; Balic R; Gilbert R G; Griffiths M; Ho C C; Monteiro M J; Taylor J R (Journal of Natural Rubber Research, 1997)
A novel class of materials, comprising an artificial polymer inside natural rubber latex particles, so that the new polymer is extensively grafted to the cis-polyisoprene, can be made if the artificial polymer is of very low water solubility, with the natural rubber latex (NRL) used as seed. This avoids the problem of secondary particle formation and subsequent engulfing of the resulting precursor particle into the pre-existing latex particles, which gives inhomogeneities in the conventional means of making modified NRL through such seed technology.
Keywords: Emulsion polymerisation; Natural rubber latex